On Some Difference Sequence Spaces of Bi-complex Numbers - Parajuli, Purushottam; Pahari, Narayan Prasad; Ghimire, Jhavi Lal; Jaiswal, Molhu Prasad (Journal of Nepal Mathematical Society, 2025)
In this paper, we study difference sequence spaces ℓ_∞(∆), c(∆), and c_0(∆) in the context of bicomplex numbers. We show that these spaces form a linear vector space. Further, we explore their algebraic, topological, and geometric properties. Several illustrative examples are also provided to support the results.